Effect of Spontaneous Polarization Charges on the Electron Mobility in ZnO Surface Quantum Wells - Tien, Nguyen Thanh; Tuan, Le; Quang, Doan Nhat (Communications in Physics, 2015)
We present a theoretical study of the effect due to spontaneous polarization of ZnO on the low-temperature mobility of the two-dimensional electron gas (2DEG) in a ZnO surface quantum well (SFQW). We proved that for the O-polar face this causes an attraction of electrons by the positive charges bound on the surface, while for the Zn-polar face a repulsion of them far away therefrom by the negative bound charges of the same magnitude. Accordingly, surface roughness scattering is drastically enhanced in the former case, but reduced in the latter one. Therefore, the low-% temperature 2DEG mobility in ZnO SFQWs with O-polar face is found to be dominated by surface roughness. Our theory was illustrated for the sample prepared by bombardment of the O-polar face by 100-eV hydrogen ions. The surface roughness scattering enables an explanation of the 2DEG mobility, especially, the reason of low values for the mobility in the dependence from the carrier density which has not been understood when starting from impurity scattering.